Sobrevida e fatores de risco à falhas de restaurações de resina composta em crianças com cárie de acometimento precoce - Campagna, Pâmela (2017)
In the restorative treatment of early childhood caries composite resin has been widely used, however, there is still a gap in the literature about the clinical behavior of this material in the deciduous dentition, especially in early childhood. The aim of this retrospective clinical study was to evaluate the survival and risk factors associated with failure of composite resin restorations performed in children with early-onset caries treated at the Baby Clinic of the Federal University of Santa Maria, RS. A total of 78 restorations in primary teeth from records of 24 high caries risk children (9 girls and 15 boys) were included in the study. Previous and subsequent teeth have been accepted, provided that the restoration has been performed at least a year before the evaluations and has followed the precepts and techniques recommended in the institution (UFSM). Two dentists were trained to evaluate the restorations with the intra-examiner concordance index of 0.80 to 0.87 and the inter-examiner 0.81. The restorations longevity up to 30 months of follow-up was assessed using the Kaplan-Meier survival test. Multivariate Cox regression analysis with shared frailty was used to evaluate the factors associated with failures (p<0.05).Mean survival time was 26 months (95%CI: 24.5-26.7). The survival of the restorations reached 34.8% up to 30 months, with an overall annual failure rate of the 20.0%. Restorations involving two or more surfaces had 2.50 times more risk of failure than restorations placed in cavities involving single surface (p=0.03).Restorations performed in vital teeth had a lower risk of failure than those performed in teeth underwent pulp intervention (HR: 0.25; 95%CI: 1.00-0.65; p = 0.00). Patients with plaque index more than 20% had more risk of failure in their restorations (HR: 3.63; 95% CI 1.29-10.2; p=0.01). Resin composite restorations placed in patients with early childhood caries presented restricted survival after 30 months of follow-up. Clinical variables such as number of restored surfaces, pulp therapy and poor biofilm control may play an important role in the survival of composite restorations performed in younger children with high caries risk.